Kreativitas Pesan Kampanye dalam Produk Ekonomi Kreatif Video Musik Animasi “Sabda Alam" - Syahid, Syahid; Wardani, Winny Gunarti Widya; Akbar, Taufiq (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2023)
The economic creative product is the result of human resources’ work that is based on creativity, renewable, and unlimited. These products originate from the development of ideas and talents to produce competitive outputs in the creative industry. Creative economic products are considered capable of making economic contributions as they become part of the solution to societal issues. This study examines "Sabda Alam," an animated music video created by students at SMK Raden Umar Said (RUS) Kudus which has gained international appreciation. This product is interesting to research because it is designed as a campaign message about the protection of endemic birds in Indonesia. Quantitatively, a survey gathered input from 150 respondents, assessing the audience’s perception of the campaign’s message. Qualitatively, the analysis employed the CAN (Connectedness, Appropriateness, Novelty) approach to identify elements within the campaign’s creativity. The study reveals that these elements are conveyed through a simple campaign message, unexpected scenes, realistic visuals, and emotional engagement through the animated storyline. This research serves as an academic reference on the potential of creative economic products to address environmental issues through creative, informative, and persuasive campaigns, fostering public awareness.